2015
DOI: 10.1055/s-0035-1568139
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Auricular Malformations: Description of Anomalies and Syndromes

Abstract: Half of the malformations in the ear, nose, and throat region affect the ear. Malformations of the external ear (pinna or auricle with external auditory canal [EAC]) are collectively termed microtia. Microtia is a congenital anomaly that ranges in severity from mild structural abnormalities to complete absence of the external ear (anotia). Microtia occurs more frequently in males (∼2 or 3:1), is predominantly unilateral (∼70-90%), and more often involves the right ear (∼60%). The reported prevalence varies geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 30 publications
1
57
0
Order By: Relevance
“…Due to the variable expressivity, there is no consensus regarding the minimum diagnostic criteria for OAVS . Generally, the minimal criteria for OAVS are considered to be unilateral microtia, hypoplasia of the mandible, epibulbar dermoids, and anomalies of the cervical spine . Nearly all patients with OAVS have some degree of hemifacial microsomia, resulting from maxillary and/or mandibular hypoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the variable expressivity, there is no consensus regarding the minimum diagnostic criteria for OAVS . Generally, the minimal criteria for OAVS are considered to be unilateral microtia, hypoplasia of the mandible, epibulbar dermoids, and anomalies of the cervical spine . Nearly all patients with OAVS have some degree of hemifacial microsomia, resulting from maxillary and/or mandibular hypoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Although Matsuo K et al [8] in Japan found that different types of CADs have the tendency of natural improvement, there is still a lack of high-quality studies to demonstrate the degree of natural improvement. Therefore, it is suggested that treatment and correction should be carried out as early as possible [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Grade III displays only soft tissue rudiments, with no definable structures of the auricle. Grade IV is the extreme case in which the external ear and auditory canal are absent, a condition called anotia [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many syndromic microtia patients present with inner ear malformations, including branchio-oculofacial, branchio-oto-renal/branchio-otic, CHARGE (coloboma, heart defects, choanal atresia, retarded growth and development, genital abnormalities, ear anomalies), Nager (preaxial acrofacial dysostosis), Treacher Collins, Wildervanck (cervico-oculo-acoustic), LAMM (congenital deafness, inner ear agenesis, microtia, microdontia) and lacrimo-auriculodento-digital (LADD) syndromes, among others. The frequent malformations of the inner ear are common cavity, cochlear aplasia, Mondini defect, enlarged vestibular aqueduct, abnormal/absent semicircular canals, and bulbous IAC (internal auditory canal) [ 7 ]. Conductive hearing loss, sensorineural hearing loss, and mixed hearing loss can all be found in microtia patients [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation